ACTR-13. FINAL RESULTS WITH CHEMORADIOTHERAPY FOR ANAPLASTIC OLIGODENDROGLIAL TUMORS FROM NRG ONCOLOGY/RTOG 9402. (11th November 2019) - Lassman, Andrew; Won, Minhee; Gregory Cairncross, J; Shaw, Edward; Ashby, Lynn; Souhami, Luis; Laack, Nadia; Fink, Karen; Macdonald, David; Bahary, Jean-Paul; Hartford, Alan; Whitton, Anthony; et al.
Abstract: BACKGROUND: Adding intensive-procarbazine, lomustine, and vincristine (iPCV) to radiotherapy (RT) prolonged progression-free (PFS) and overall survival (OS) for patients with 1p19q codeleted anaplastic oligodendroglial tumors (AOTs); some benefit was also observed for IDH-mutant non-codeleted cases (Cairncross et al 2013, 2014, 2016). Now, 25 years after study activation, we updated survival, further assessed IDH as a predictive biomarker, and are exploring the benefit from vincristine. METHODS: Eligible adults (KPS ≥ 60, adequate end-organ function) were randomized to pre-RT iPCV (4 cycles x 6 weeks each) vs. RT alone, stratified by age (< or ≥ 50), KPS (60–70 or ≥ 80), and level of anaplasia. Histology (anaplastic oligodendroglioma/oligo-astrocytoma required) and biomarkers (IDH and 1p19q, post-hoc) were determined centrally. Survival was estimated by Kaplan-Meier and Hazard Ratios (HRs) by Cox-regression. RESULTS: Overall (n=289), median follow-up was 16.4 years vs. 11.3 years at last report. In codeleted cases, 40% randomized to iPCV remained alive vs. 53% at last report; 5, 10, and 14 year-PFS and -OS rates were 62%, 50%, 41% and 70%, 57%, 46%, respectively; and iPCV unequivocally prolonged PFS (median 9.8 vs. 2.9 years, HR 0.46, 95% CI 0.3–0.7, p< 0.001) and OS (median 13.2 vs. 7.3 years, HR 0.61, 95% CI 0.40–0.94; p=0.02). With IDH mutation but without codeletion (n=66), iPCV prolonged PFS (median 2.8 vs. 1.9 years, HR 0.58, 95% CI 0.34–0.99, p=0.046); OS was longer with a trend for significance (median 5.5 vs. 3.3 years, HR 0.6, 95% CI 0.34–1.03, p=0.06) on this underpowered exploratory post-hoc analysis. CONCLUSION: For codeleted AOTs, long-term analyses confirmed that pre-RT iPCV produced meaningful and significant prolongations of PFS and OS. With IDH mutation but without codeletion, iPCV significantly prolonged PFS and showed a trend for prolonged OS. The value of vincristine is being assessed. Supported by NCI grants U10CA180868, U10CA180822, U24CA196067, and UG1CA189867.